Effects of Genistein and Exercise Training on Brain Damage Induced by a High-Fat High-Sucrose Diet in Female C57BL/6 Mice. (17th May 2022) - Li, Rongzi; Ding, Xiaowen; Geetha, Thangiah; Fadamiro, Moni; St Aubin, Chaheyla R.; Shim, Minsub; Al-Nakkash, Layla; Broderick, Tom L.; Babu, Jeganathan Ramesh
Abstract : In recent decades, a shift in the nutritional landscape to the Western-style diet has led to an unprecedented rise in the prevalence of obesity and neurodegenerative diseases. Consumption of a healthy diet and engaging in regular physical activity represents safe and affordable approaches known to mitigate the adverse consequences of the Western diet. We examined whether genistein treatment, exercise training, and a combination treatment (genistein and exercise training) mitigated the effects of a Western diet-induced by high-fat, high-sugar (HFHS) in brain of female mice. HFHS increased the amyloid-beta (A β ) load and phosphorylation of tau, apoptosis, and decreased brain-derived neurotrophic factor (BDNF) levels. Exercise training and genistein each afforded modest protection on A β accumulation and apoptosis, and both increased BDNF. The greatest neuroprotective effect occurred with combination treatment. BDNF and all markers of A β accumulation, phosphorylation of tau, and apoptosis were improved with combined treatment. In a separate series of experiments, PC12 cells were exposed to high glucose (HG) and palmitate (PA) to determine cell viability with genistein as well as in the presence of tamoxifen, an estrogen receptor antagonist, to assess a mechanism of action of genistein on cell apoptosis. Genistein prevented the neurotoxic effects of HG and PA in PC12 cells and tamoxifen blocked the beneficial effects of genistein on apoptosis. Our results indicate the beneficial effects of genistein and exercise training on HFHS-induced brain damage. The benefits of genistein may occur via estrogen receptor-mediated pathways.